Developing and Validating an Instrument for Measuring Pre-Service Science Teachers’s Environmental Knowledge - Febrianawati Yusup (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2024)
Environmental literacy assessment of pre-service science teacher candidates is no patent, so there is a need to develop special instruments for science teachers candidates that are in accordance with the character of the subject to be studied. This study aimed to develop a valid and reliable instrument to be used for measuring science teacher candidate’s environmental knowledge of environmental literacy. This instrument was validated by two experts and widely pilot testing involves 31 science teacher candidates from biology teacher candidates, physics teacher candidates, and chemistry teacher candidates. Results of content validation in this study, show that experts suggested to revise five questions. Results of criteria validation in this study by mean of Cronbach Alpha test show that only seven of 15 questions that can be used to assess the environmental knowledge of science teacher candidates. One question item received without correction and six other questions received with revision. The reliability of the instrument was measured using the Kuder Richardson 20 (KR 20) test and the result was 0.63, which means the instrument was acceptable for use. The results of this study indicate that the instrument is valid and reliable for the assessment of science teacher candidate’s environmental knowledge. However, this instrument still has to be tested again if it is to be used to measure the validity and reliability of the instrument before to be used to measure another data.